Return on Asset Analysis in Assessing Performance: Transforming Organizational Financial Performance - Achmad Febrianto; Ayu Aisyatun Nabila (Al-Qalam Institue, 2025)
This study evaluates the financial performance of Bank Negara Indonesia Tbk through an analysis of Return on Assets (ROA), with implications for management education. The method employed is a descriptive quantitative approach utilizing secondary data from financial statements published through the Indonesia Stock Exchange. ROA is calculated using the standard formula (Net Income/Total Assets) × 100% to measure the effectiveness of asset utilization in generating profitability. The results reveal a highly impressive performance transformation, with ROA increasing from a low of 0.37% in 2020 to 2.00% in 2023, surpassing the banking industry standard of 1.5%. Net income experienced a remarkable expansion of 664%, from Rp 3,280,403 million to Rp 21,779,523 million, while total assets steadily grew by 21.9%, from Rp 891,337,425 million to Rp 1,086,663,986 million. The 5.4-fold increase in ROA indicates highly effective asset management optimization. The study concludes that Bank Negara Indonesia Tbk demonstrated exceptional resilience in facing the COVID-19 pandemic crisis and successfully leveraged the economic recovery momentum to achieve outstanding performance. Implications for education management: This research emphasizes the importance of strategic management and financial analysis, which can be integrated into management education to equip future leaders with the skills necessary to navigate crises and optimize resource utilization effectively.